Modeling and characterization of piezoelectric beams based on an aluminum nitride thin‐film layer. Issue 1 (15th October 2015) - Herth, Etienne; Algré, Emmanuelle; Rauch, Jean‐Yves; Gerbedoen, Jean‐Claude; Defrance, Nicolas; Delobelle, Patrick
Abstract : This paper presents a method to determine the mechanical properties of piezoelectric thin films. The vibrational behavior of microcantilevers and clamped–clamped beams actuated by aluminum nitride (AlN) piezoelectric films were analyzed in order to investigate the suitability of these devices as characterization tools. Different geometries of resonators composed of a free‐standing structure made up of a TiPt/AlN/TiPt piezoelectric stack were tested. The out‐of‐plane motion of the resonators was assessed by laser Doppler vibrometry. An AlN Young's modulus of about 200 GPa was extracted from resonance‐frequency measurements by means of Comsol software simulations that allow taking into account AlN underetching. This value of Young's modulus was compared to the one measured by a nanoindentation technique. The quality of crystallinity was also assessed using X‐ray diffraction (XRD) measurements. We then estimated the residual stress (about 200 MPa) using an interferometry measurement.